Biosynthesis, characterization, and antifungal activity of plant-mediated silver nanoparticles using Cnidium monnieri fruit extract - Ye, Mingqi; Yang, Wenwen; Zhang, Minxin; Huang, Huili; Huang, Aiwen; Qiu, Bin (Frontiers in Microbiology, 2023)
The present study describes a novel method for green synthesis of silver nanoparticles using Cnidium monnieri (CM-AgNPs). Cnidium monnieri fruit is an excellent anti tinea drug that can be used externally to treat superficial fungal infections in the human body. The aqueous ethanolic extract of Cnidium monnieri fruit was prepared and employed in the synthesis of stable silver nanoparticles via biological reduction method. The synthesis conditions of CM-AgNPs was systematically optimized using Box–Behnken design. CM-AgNPs were well characterized by UV-spectroscopy and X-ray powder diffraction (XRD), and it was confirmed that the synthesized particles were AgNPs. The possible functional groups required for the reduction and stabilization of CM-AgNPs in the extract were identified through FTIR spectrum. The size of CM-AgNPs structure was confirmed to be approximately 44.6 nm in polydisperse spherical shape through scanning electron microscopy (SEM), transmission electron microscopy (TEM), and laser dynamic light scattering (DLS). Further, the minimum inhibitory concentration 90% (MIC90) ratios values of Cm-AgNPs against Trichophyton rubrum (7 d), T. mentagrophytes (7 d) and Candida albicans (24 h) were 3.125, 3.125, and 0.78125 μg/mL, respectively, determined by the broth micro dilution method. Finally, the result was concluded that the synthesized AgNPs could be further evaluated in large scale as a potential human topical antifungal agent.